Improved Helicobacter pylori Eradication Rate of Tailored Triple Therapy by Adding Lactobacillus delbrueckii and Streptococcus thermophilus in Northeast Region of Thailand: A Prospective Randomized Controlled Clinical Trial. (8th June 2015) - Tongtawee, Taweesak; Dechsukhum, Chavaboon; Leeanansaksiri, Wilairat; Kaewpitoon, Soraya; Kaewpitoon, Natthawut; Loyd, Ryan A.; Matrakool, Likit; Panpimanmas, Sukij
Abstract : Background and Aim . To evaluate the effect of Lactobacillus delbrueckii subsp. bulgaricus and Streptococcus thermophilus to Helicobacter pylori eradication in different periods of therapeutic protocol. Methods . Infected patients were randomized to one-week tailored triple therapy (esomeprazole 20 mg bid, clarithromycin 500 mg bid/metronidazole 400 mg tid if clarithromycin resistant, and amoxicillin 1000 mg bid) with placebo (group 1, n =100 ); one week of pretreatment with probiotics (group 2, n =100 ); and one week of pretreatment with probiotic followed by one week of the same probiotics after treatment (group 3, n =100 ). Result . PP analysis involved 292 patients, 98 in group 1, 97 in group 2, and 97 in group 3. Successful eradication was observed in 229 patients; by PP analysis, the eradication rates were significantly higher (P <0.01, 95% CI; 0.71–0.97) in group 2 and group 3 than group 1. ITT analysis eradication rates were significantly higher in group 2 and group 3 than group 1 (P <0.01 95% CI; 0.72–0.87), and there is no significant difference between the three groups (P =0.32 ) in terms of adverse events. Conclusion . Adding probiotics before or before and after tailored treatment can improve Helicobacter pylori eradication rates. This trial is registered with Thai Clinical Trials Registry number:TCTR20141209001 .